2008
DOI: 10.1590/s0034-71672008000300002
|View full text |Cite
|
Sign up to set email alerts
|

Registros sobre dor pós-operatória em crianças: uma análise retrospectiva de hospitais de Londrina, PR, Brasil

Abstract: All surgical procedures involve tissue lesions, manipulation of structures and organs, causing pain which can be minimized during the process. The objective of this study is to characterize, retrospectively, the process of managing post-operative pain based on 300 medical records of 280 children, who underwent surgery in 2004, in 3 hospitals located in Londrina, PR, Brazil. The study revealed that only a few nurses document post-operative pain, and that the majority of the records were made by nursing aides or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
17

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 6 publications
0
8
0
17
Order By: Relevance
“…In the face of this work structure, many children may suff er pain due to not being appropriately assessed, which disrespects the ethical and legal du es to alleviate the suffering caused by pain, according to the Brazilian Rights of the Hospitalized Child and Adolescent (14) .…”
Section: Rev Esc Enfermmentioning
confidence: 99%
See 1 more Smart Citation
“…In the face of this work structure, many children may suff er pain due to not being appropriately assessed, which disrespects the ethical and legal du es to alleviate the suffering caused by pain, according to the Brazilian Rights of the Hospitalized Child and Adolescent (14) .…”
Section: Rev Esc Enfermmentioning
confidence: 99%
“…One study found that 8.0% of the children had received analgesia for the inser on of a central catheter, 100.0% for a thoracic drain, while none received analgesia for arterial, venous, capillary and lumbar puncture or for tracheal intuba on -the authors of the study emphasizing that in adults, these procedures are rarely carried out without analgesia (21) -which is similar to the fi ndings of the present study. Unfortunately, this under-treatment of pain is rou ne in various services and studies confi rm this reality in the treatment of children (6,(14)(15)20) .…”
Section: Rev Esc Enfermmentioning
confidence: 99%
“…Apesar da busca pelo entendimento do mecanismo, acesso e manejo da dor infantil, pouco do conhecimento obtido em pesquisas tem sido observado na prática da enfermagem (TACLA; HAYASHIDA; LIMA, 2008;WALCO;GOLDSCHNEIDER, 2008).…”
Section: Introductionunclassified
“…Mesmo assim, crenças errôneas a respeito do assunto são constantes, o que compromete diretamente a assistência na avaliação e manejo dessa dor. Entre os mitos comuns encontramos: a criança sente menos dor que o adulto, a criança se acostuma ou tolera a dor mais facilmente que o adulto, o uso de opióides pode ser viciante, a avaliação da dor na criança é difícil e despende muito tempo, entre outras (TACLA; HAYASHIDA; LIMA, 2008;FINLEY;2010). Na verdade, a criança sente dor tanto quanto um adulto ou até mais, visto que possui vias da dor e sistemas neuroquímicos associados à transmissão e modulação da dor intactos e funcionantes, por outro lado, seus mecanismos de controle inibitório da dor ainda estão imaturos (LEÃO et al, 2008;WHALEY;WONG, 2007).…”
Section: Introductionunclassified
“…Em se tratando de pacientes ortopédicos, as ferramentas para o gerenciamento da dor são as farmacológicas (administração de medicamentos), e não farmacológicas (mobilidade e movimentação, acupuntura, massagem terapêutica, relaxamento, posicionamento e conforto). Dentre as alternativas para analgesia farmacológica no pós-operatório de cirurgia ortopédica destacam-se a infusão de analgésico por via peridural, a analgesia controlada pelo paciente (ACP) e a administração por via venosa de medicação; além disso, as intervenções de Enfermagem podem representar algumas das medidas não farmacoló-gicas de controle e melhoria dos quadros dolorosos 3,6,7 . O papel da Enfermagem no controle da dor pós-operatória do paciente ortopédico consiste na avaliação da intensidade e na adoção de estratégias para minimizar o desconforto, mediante o planejamento dos cuidados, levando em consideração as alterações dos sinais vitais, das condições físicas e emocionais e do quadro doloroso propriamente dito.…”
Section: Introductionunclassified